HUBUNGAN STATUS GIZI DAN USIA MENARCHE DENGAN KEJADIAN DISMENORE PADA REMAJA PUTRI DI SMAN 1 BANGKINANG KOTA TAHUN 2018 - fitri apriyanti (Jurnal Maternitas Kebidanan, 2018)
The incidence of dysmenorrhea is very large. On average more than 50% of women experience it, in Indonesia 72.89%. According to the World Health Organization (WHO) in 2013 the incidence of dysmenorrhea was 1. 769. 425 people (90%) of women who experienced dysmenorrhea, there were 10-15% of those with severe dysmenorrhea, on average nearly 50% of women experienced it. Risk factors for dysmenorrhea during menstruation are too early menstruation, nutritional status and family history. The purpose of this study was to determine the relationship of nutritional status and age of menarche with the incidence of dysmenorrhea in adolescent girls in SMAN 1 Bangkinang city. The design used in this study was an analytical survey with a cross sectional approach. The population in this study were all female students of class X and XI at SMAN 1 Bangkinang city. Data collection is done using primary data. Data analysis used is univariate and bivariate. Bivariate results revealed a significant relationship between nutritional status and the incidence of dysmenorrhea in young women with p value = 0.01 or p ≤ α (0.05), whereas there was a significant relationship between the age of menarche and the incidence of dysmenorrhea in young women with p value = 0.02 or p ≤ α (0.05). Therefore it is expected that adolescents pay attention to their nutritional needs and monitor their body weight. Good nutritional status will affect the health of the body, especially in the incidence of dysmenorrhea.